Survival outcomes and prognostic factors of early-onset and late-onset metastatic esophageal cancer: a population-based study - Xinwei Guo; Lang Qin; Rui Yang; Yangchen Liu; Shaobing Zhou; Weiwei Zhao (Scientific Reports)
Abstract In recent years, the incidence of malignancies among young people, including early-onset esophageal cancer (EOEC), has been increasing globally. This study aims to compare the survival outcomes of metastatic EOEC and late-onset esophageal cancer (LOEC) and to identify prognostic factors. Patient data were collected from the Surveillance, Epidemiology, and End Results database. Hazard ratios (HR) and 95% confidence intervals (CI) were calculated using univariate and multivariate Cox regression models. Propensity score matching (PSM) was applied to balance baseline differences. The Kaplan–Meier method and log-rank test were used to compare overall survival (OS). A total of 11,738 cases of metastatic esophageal cancer were included from 2010 to 2020, with 996 EOEC patients and 10,742 LOEC patients. The mean OS for EOEC patients was 14.30 months (95% CI 12.53–16.06 months), compared to 10.89 months (95% CI 10.45–11.33 months) for LOEC patients. Multivariate Cox regression analysis revealed that marital status, histological type, tumor grade, bone metastasis, liver metastasis, surgery, and chemotherapy were independent prognostic factors for EOEC patients (p < 0.05). After adjusting for variables other than age using PSM, the results still indicated better OS for EOEC patients (p = 0.031). Further subgroup analysis showed that chemotherapy primarily influenced survival outcomes in both groups (p = 0.012). Metastatic EOEC showed better OS outcomes compared to LOEC, and EOEC patients benefited more from chemotherapy than LOEC patients.